Effects of Lean Manufacturing Implementation, Raw Material Quality, and Employee Training on the Success of Manufacturing Firms - Priyana, Yana; Arisanti, Ivon; Hadilia, Naswan (West Science Journal Economic and Entrepreneurship, 2024)
This study examines the impact of Lean Manufacturing implementation, Raw Material Quality, and Employee Training on the success of manufacturing companies through a quantitative analysis. Data was collected from 220 manufacturing firms, utilizing a Likert scale ranging from 1 to 5 to measure the variables in question. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to analyze the data. The results reveal that Lean Manufacturing, Raw Material Quality, and Employee Training all have positive and significant effects on the success of manufacturing firms, with Lean Manufacturing emerging as the most influential factor. The findings suggest that a holistic approach, integrating lean practices, high-quality raw materials, and continuous employee development, is essential for achieving superior performance in the manufacturing sector. This study contributes to the literature by providing empirical evidence on the synergistic effects of these critical factors and offers practical insights for industry practitioners and policymakers.